Disclosing Labor Demand: Evidence from Online Job Postings - Sran, Gurpal S. (The Accounting Review, 2025)
ABSTRACT I study disclosure choices in job postings and the following tradeoff: detailed postings inform and attract optimal job applicants (labor market channel) but could simultaneously inform competitors in labor and product markets (proprietary costs channel). First, I provide evidence consistent with a proprietary costs channel. Conditional on a set of labor demand characteristics, private firms and redacting firms write shorter postings (i.e., less contextual specificity), and postings are more often anonymous in high-secrecy industries. Then, I exploit the implementation of federal trade secrecy protections as a shock to both innovation and opacity incentives to assess the balance between the two channels. After implementation, firms demand higher skill levels for innovative jobs, consistent with protections spurring innovation. However, contextual specificity decreases, in line with the proprietary costs channel, as protections are maximized when firms remain opaque regarding innovation. This decrease is attenuated in tight labor markets, consistent with the proposed tradeoff. Data Availability: Data used in this study are available from sources identified in the manuscript. JEL Classifications: D80; J23; J24; J60; M41; M51; O31; O34.